2004
DOI: 10.1111/j.1745-7599.2004.tb00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of and Problems With Primary Care Interactions Experienced by an Ethnically Diverse Group of Woman

Abstract: The women strongly valued caring clinicians. Caring, according to these women, is demonstrated when clinicians treat women as equals and show respect for their individual knowledge and life experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 31 publications
(49 reference statements)
2
29
0
Order By: Relevance
“…Despite this, Australian consumers are accepting of a broad range of activities that could be undertaken by nurse practitioners in primary health‐care settings. In common with international evidence, women were more accepting of the nurse practitioner's role …”
Section: Discussionmentioning
confidence: 92%
“…Despite this, Australian consumers are accepting of a broad range of activities that could be undertaken by nurse practitioners in primary health‐care settings. In common with international evidence, women were more accepting of the nurse practitioner's role …”
Section: Discussionmentioning
confidence: 92%
“…Other research has found that physicians engage in verbally dominant and less patient‐centered communication with their African American patients as compared to white patients (Johnson, Roter, Powe, & Cooper, 2004). There are few studies that examine the perceptions of African American patients regarding NPs, and those that do exist have mixed results (Alexander, 2004; Benkert et al, 2004). Benkert and colleagues found that African American women expected and found most European American NPs in this study of race‐discordant primary care relationships to be kind, respectful, and trustworthy, while work by Alexander revealed that some NPs displayed behaviors that diminished trust, such as sharing a patient’s personal information with others.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report an evidence that men are less satisfied with the received medical care than women [19], and some report that women are more dissatisfied from medical care than men [20]. A metaanalysis of patient satisfaction concludes that there is no average gender difference in satisfaction with medical care [21].…”
Section: Discussionmentioning
confidence: 99%